Perancangan Aplikasi Pengajuan Kerusakan Peralatan Kerja Berbasis Web - Agustina, Merry (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2024)
This research resulted in a web-based information system that can be used for processing office equipment damage submissions at PT. Pelabuhan Indonesia (Persero) Regional II. The system was developed using the PHP (Hypertext Preprocessor) programming language and MySQL, and it was based on the waterfall method for its development process. With features such as damage submission for work equipment, submission log management, repair and maintenance, and report generation, this application is expected to improve efficiency in managing equipment damage and provide better services to employees